News and Civic Opera Buildings, Chicago, Ill. (Geston Bros.)
The new home of The Chicago Daily News at Madison, Canal Washington and the river. This structure, which is 25 stories in height, houses the plant and all editorial and business departemtns of The Daily News. 20 North Wacker Drive Building, Chicago. 42-story office building costing $20,000,000. Contains 3,600 seat auditorium and small theatre. This building houses the Chicago Civic Opera Company.